Christian medicine in modern Shanghai - WANG Ziyin, (Journal of Research for Christianity in China (JRCC), 2025)
Shanghai, after its opening of commercial port, had become the best choice for missionaries to expand Western medical career. The introduction of Western medicine not only affected the medical treatment view of Shanghai residents, but also laid a foundation for establishing a new modern medical system. This paper focuses on the relationship between Christian medical treatment and traditional Chinese medicine, which both was market competitors as well as mutual influencer. It further explores the modern medical career in Shanghai through the elaboration of Christian medical service development in Shanghai and its connection with traditional Chinese medicine.
Keywords: Shanghai; Christian Hospital; Medical Education; Perspectives on Seeking Treatment in Traditional Chinese and Western Medicine